Enhanced multiferroicity and narrow band gap in B-site Co-doped Aurivillius Bi5FeTi3O15. Issue 1 (January 2019) - Zuo, Xuzhong; Zhu, Shunjin; Bai, Jin; He, Enjie; Hui, Zhenzhen; Zhang, Peng; Song, Dongpo; Song, Wenhai; Yang, Jie; Zhu, Xuebin; Dai, Jianming
Abstract: The effects of Co ions substitution on the structural, multiferroic, dielectric, and optical properties of Aurivillius Bi5 FeTi3 O15 are investigated. High resolution transmission electron microscope measurements imply that Bi5 FeTi2 Nb0.5 Co0.5 O15 (BFTNCO) exhibits a typical four-layered Aurivillius structure. The co-doping of Nb/Co ions at Ti sites is found to induce the lattice distortion. In comparison with Bi5 FeTi3 O15 and Bi5 Fe0.5 Co0.5 Ti3 O15, the sample BFTNCO shows a more superior multiferroicity with the remanent magnetization M r and polarization P r of 76.4 memu/g and 10.2 μC/cm 2, respectively. The improved multiferroicity can be ascribed to reduced oxygen vacancy, large lattice distortion and large grain size. In addition, a relatively narrow optical band gap E g can be obtained as 2.30 eV for BFTNCO. The decreased E g in BFTNCO can be attributed to large lattice distortion and the overlap of Co 3 d state with Ti t 2g state. These results reveal that Ti-site doped Aurivillius phase may be the potential candidates for exploring excellent room-temperature multiferroics with narrow band gap.